Postmodernism and the Human Subject: The Return of the Repressed - Noonan, Jeffrey (My University, 1996)
According to postmodern philosophy, the great political errors and crimes of the modern period may be traced back to the essentialism of modern thought. Modernity sought to base universal political projects upon a universal definition of humanity as a rationally self-determining species. However, such a view of humanity is opposed to the real cultural differences which characterize real communities. The essentialist picture of human being, far from furthering the work of freedom, legitimates the suppression of any differences judged to be unessential. Postmodernism hopes to overcome the suppression of differences by rejecting the notion of subjecthood upon which modernity rested. However, by giving up the idea that humanity is essentially self-determining, postmodern politics become incoherent. The concern for the oppressed which animates postmodern philosophy pre-supposes what postmodern critique denies-a real, universal human capacity to alter circumstances in accordance with self-given plans.
*page 147 not removed from text
Keywords: Postmodernism; human subject